2023
DOI: 10.1007/s43678-022-00414-w
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with 1-week revisit among emergency department patients with alcohol withdrawal

Abstract: Background Approximately one-quarter of emergency department (ED) visits for alcohol withdrawal result in unscheduled 1-week ED return visits, but it is unclear what patient and clinical factors may impact this outcome Methods From January 1, 2015, to December 31, 2018, at three urban EDs in Vancouver, Canada, we studied patients who were discharged with a primary or secondary diagnosis of alcohol withdrawal. We performed a structured chart review to ascertain patient characteristics, ED treatments, and the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Despite well documented evidence that children start using alcohol and other substances early [ 7 , 12 , 13 ], additional evidence indicates that individuals with alcohol and substance use disorders often access the health care system for reasons other than seeking care for substance use problems [ 26 , 27 ]. Many do not seek specialty treatment but they are over-represented in many general health care settings, signalling that the health care system is an important entry point for recognising and later addressing these underlying disorders [ 27 , 28 ]. Some literature on the prevalence of substance use among children in the community as well as facility settings is available [ 11 , 29 – 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite well documented evidence that children start using alcohol and other substances early [ 7 , 12 , 13 ], additional evidence indicates that individuals with alcohol and substance use disorders often access the health care system for reasons other than seeking care for substance use problems [ 26 , 27 ]. Many do not seek specialty treatment but they are over-represented in many general health care settings, signalling that the health care system is an important entry point for recognising and later addressing these underlying disorders [ 27 , 28 ]. Some literature on the prevalence of substance use among children in the community as well as facility settings is available [ 11 , 29 – 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…As emergency care providers, it can be frustrating and seem futile to treat—or not treat—patients with AUD, as the ED often lacks the necessary resources to provide patients with interventions, pharmacotherapy, and access to addiction services. As Scheuermeyer et al [ 2 ] describe the 15% one-week ED revisit rate for those experiencing alcohol withdrawal, it calls attention to the ‘revolving door’ nature of current ED practices for patients presenting with AUD. Emergency care providers may have completed the CAGE questionnaire and identified that a patient has AUD, but now what?…”
mentioning
confidence: 99%
“…In addition, they highlight the underprescription of pharmacotherapy. Less than 50% of their patient population was prescribed benzodiazepines at discharge for a diagnosis of alcohol withdrawal [ 2 ]. Is that due to emergency care providers underrecognizing AUD and its consequences?…”
mentioning
confidence: 99%
See 2 more Smart Citations